Nash Equilibrium and the Evolution of Preferences - Jeffrey C. Ely; Okan Yilankaya (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
A population of players of players is randomly matched to play a normal form game G. The payoffs in this game represent the fitness associated with the various outcomes. Each individual has preferences over the outcomes in the game and chooses an optimal action with respect to those preferences. However, these preferences needn't coincide withe the fitness payoffs. When evolution selects individuals on the basis of the fitness of the actions they choose, the distribution of aggregate play must be a Nash equilibrium of G. Weak additional assumptions on the evolutionary process imply perfect equilibrium.
Keywords: 330